2007
DOI: 10.1128/mcb.00658-06
|View full text |Cite
|
Sign up to set email alerts
|

The SYT-SSX Fusion Protein Down-Regulates the Cell Proliferation Regulator COM1 in t(x;18) Synovial Sarcoma

Abstract: Chromosomal translocations are frequently associated with soft-tissue sarcomas. Fusion proteins generated by such translocations often play critical roles in tumorigenesis. Therefore, it is important to understand the function of the fusion protein to develop therapeutic interventions. The t(X;18)(p11.2;q11.2) translocation found in synovial sarcomas results in a fusion between the SYT gene on chromosome 18 and an SSX gene on the X chromosome. Although SYT-SSX fusion proteins appear to trigger synovial sarcoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 28 publications
2
34
0
Order By: Relevance
“…Ishida and colleagues (39) have recently shown both SS18 and SS18-SSX to be present at the COM1 promoter in HEK293 cells expressing hemagglutinin-tagged SS18 and SS18-SSX. In their study, SS18-SSX was shown to repress COM1 in HeLa cells stably expressing the fusion oncoprotein.…”
Section: Discussionmentioning
confidence: 99%
“…Ishida and colleagues (39) have recently shown both SS18 and SS18-SSX to be present at the COM1 promoter in HEK293 cells expressing hemagglutinin-tagged SS18 and SS18-SSX. In their study, SS18-SSX was shown to repress COM1 in HeLa cells stably expressing the fusion oncoprotein.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Ishida et al found that synovial sarcomas had decreased expression of NUPR1 [35]; and restoring the expression of NUPR1 resulted in reduced proliferation and colony formation accompanied by increased apoptosis, suggesting that NUPR1 plays a growth inhibitory role in synovial sarcoma growth.…”
Section: Anti-tumor and Growth Inhibitory Properties Of Nupr1mentioning
confidence: 95%
“…For the small interfering RNA (siRNA) experiments, 20 nmol/L of control siRNA (Qiagen) and NRF2-specific siRNA (SI03246950; Qiagen) were used. Transfection was performed as described previously (17). RT-PCR was performed after 3 days and cell numbers were counted after 7 days.…”
Section: Methodsmentioning
confidence: 99%